2012
DOI: 10.1063/1.4724344
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube-based charge-controlled speed-regulating nanoclutch

Abstract: In this paper, a carbon nanotube-based charge-controlled speed-regulating nanoclutch (CNT-CC-SRNC), composed of an inner carbon nanotube (CNT), an outer CNT, and the water confined between the two CNT walls, is proposed by utilizing electrowetting-induced improvement of the friction at the interfaces between water and CNT walls. As the inner CNT is the driving axle, molecular dynamics simulation results demonstrate that CNT-CC-SRNC is in the disengaged state for the uncharged CNTs, whereas water confined in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…10. The varying trend is in agreement with the pure water molecules confined in CNTs, 32 while the difference is that the threshold of the charge magnitude is 1.2 e for the pure water confined in the CNT walls. This result can also be interpreted by the relationship between the shear stress and shear rate in Fig.…”
Section: Influence Of the Charge Magnitudesupporting
confidence: 71%
See 2 more Smart Citations
“…10. The varying trend is in agreement with the pure water molecules confined in CNTs, 32 while the difference is that the threshold of the charge magnitude is 1.2 e for the pure water confined in the CNT walls. This result can also be interpreted by the relationship between the shear stress and shear rate in Fig.…”
Section: Influence Of the Charge Magnitudesupporting
confidence: 71%
“…32,35 Here we take into account the influence of the charge magnitude on the boundary slip and accumulation of the fullerene molecules within the fullerene-water NFs in Couette model with the shearing velocity of 300 m/s. It can be observed that the boundary slip velocity is not varied monotonically with the charge magnitude on graphene sheets, which decreases with the charge magnitude below a threshold of 0.6 e, and then increase appreciably, as shown in Fig.…”
Section: Influence Of the Charge Magnitudementioning
confidence: 99%
See 1 more Smart Citation
“…The five CNTs with different diameters are considered to examine the size dependence of the mechanical property. In addition, it has been proved that the electricity, the ubiquitous environment in biological molecules, could make an obvious effect on the water molecules inside the CNTs 19 20 21 . Therefore, the electric field is also taken into account in the MD simulation reported here.…”
mentioning
confidence: 99%
“…[4][5][6][7][8]. Molecular dynamics (MD) simulations have explored the effects of an electric field on nanochannel transportation characteristics, where an electric field can be achieved by assigning charges near a nanochannel [9][10][11][12][13][14][15], adding ions to the water phases on both sides of a nanotube [16][17][18], or directly using MD software such as NAMD [8,19,20], GROMACS, etc. [21][22][23].…”
Section: Introductionmentioning
confidence: 99%